Relationship between dietary factors and hyperlipidemia in a general Japanese population : the Hisayama study - Kiyohara, Yutaka; Tanizaki, Yumihiro; Shirota, Tomoko; Yonemoto, Koji; Uchida, Kazuhiro; Kubo, Michiaki; Morita, Tomomi; Iida, Mitsuo (Japanese Journal of Cardiovascular Disease Prevention, 2005)
PURPOSE : To investigate the relationship between dietary factors and serum low-density lipoprotein cholesterol (LDLC) levels in a general population. METHODS : In cross-sectional analysis of 2445 men and woman aged 40 to 79 years selected from a community of Hisayama Town, we compared dietary factors between subjects with hyperlipidemia (LDLC ≥ 140 mg/dl) and those without hyperlipidemia. RESULTS : After adjustment for non-dietary factors, such as age, body mass index, fasting plasma glucose, smoking habits, alcohol intake, and physical activity with logistic regression model, energy-adjusted intake of total fat (odds ratio for an increase of 1SD, 1.21; 95% confidence interval, 1.06-1.39) and dietary oils and fats (1.22; 1.06-1.39) remained as significant independent relevant factors of hyperlipidemia in men, while animal protein (1.15; 1.02-1.29), sodium (0.86; 0.77-0.96), milk (1.18; 1.05-1.34), sugar (1.13; 1.01-1.27), and rice (0.88; 0.78-0.99) were significant independent relevant factors in women. In men, the age-adjusted energy ratios of protein and fat were significantly higher for subjects with hyperlipidemia compared to normal subjects, while energy ratio of animal protein were significantly increased in women with hyperlipidemia. Saturated fatty acid (S) and monounsaturated fatty acid intakes were significantly higher in subjects with hyperlipidemia than in normal subjects for both men and women. In addition, cholesterol and polyunsaturated fatty acid (P) intakes were significantly higher in women with hyperlipidemia. The P/S ratio were significantly decreased in woman with hyperlipidemia than in normal subjects, however, such a difference was not observed for men. CONCLUSIONS : Our data suggest that increased fat intake is tightly associated with elevated serum LDLC levels for men, while the quality and composition of dietary fat, such as increased intake of saturated fatty acid and cholesterol, affect serum LDLC levels in women.